Unusual record of a multiple predation of the Patagonian seahorse Hippocampus patagonicus by the Narrownose smooth-hound Mustelus schmitti in Argentine coastal waters - Belleggia, Mauro (2021)
Seahorses (Genus Hippocampus) are rarely reported as prey items. Their low pop-ulation numbers, their ability to blend with the environment and their low palatability are the fea-tures making them an unsuitable option for predators. Five individuals of the Patagonian seahorseHippocampus patagonicus were found in the stomach of a single narrownose smooth-hound sharkMustelus schmittifrom a sample of 959 stomachs analyzed. This rare record in a single stomach outof hundreds analyzed suggests that these individuals might have clustered in a group which wasdetected by the opportunistic M. schmitti.